Comunicação e democracia digital: estudo comparativo da conversação nos portais Votenaweb e Isidewith - Berti, Pedro Luis Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
À medida que a internet pode contribuir para revigorar a democracia, a projeção de opiniões e a circulação de ideias sobre gestão pública, portais web que exploram as potencialidades da conversação online têm sido objetos apropriados de pesquisas que buscam conhecer as características da deliberação pública online. Esta dissertação investigou a conversação online em duas iniciativas similares, em países diferentes: VotenaWeb (Brasil) e ISideWith (Estados Unidos), que permitem a expressão de preferências sobre projetos de lei em apreciação no Parlamento. Os dados foram analisados em seis categorias de compreensão: “‘justificação’”, “reciprocidade”, “reflexividade”, “respeito”, “informação” e “tópico”. Os objetivos específicos foram: a) identificar as características da conversação virtual e indicar possíveis condições favoráveis à deliberação; b) fornecer um quadro geral sobre as características da utilização dos dois portais como plataforma para expressão política; c) apontar as possíveis diferenças na exposição de argumentos e uso de fontes de informação pelos usuários. Do portal VotenaWeb foram coletados e analisados, no total, 26.664 comentários, e do portal ISideWith, 3.528 comentários. Os resultados apresentaram diferenças significativas no uso de fontes de informação e no ambiente deliberativo construído pelos usuários.

As far as the internet can contribute to reinvigorate the democracy, the projection of opinions and the circulation of ideas about public administration, web portals that explore potentialities of online conversation have been appropriate subjects of research seeking to understand characteristics of public online deliberation. This dissertation investigated two similar initiatives in different countries: VotenaWeb (Brazil) and ISideWith (United States), which allow expression of preferences concerning bills on appreciation at parliaments. The data were analysed in six categories of comprehension, each one admitting possibilities of classification: “justification”, “reciprocity”, “reflexivity”, “respect”, “information” and “topic”. The specific aims were: a) to identify the virtual conversation characteristics and indicate possible conditions favorable to deliberation present in the each analyzed portal, according to the specialized literature; b) to provide a general framework on the use of the characteristics of the two portals as a platform for political expression; c) to point out possible differences in the expression of opinions and in the use of sources of information by citizens of each country. From VotenaWeb portal 26.664 comments were collected and analysed, and from ISideWith portal 3.528 comments were collected and analysed. The results presented significative differences in the use of sources of information and in the deliberative environment created by users.
Communication and digital democracy: comparative study of conversation in web portals VotenaWeb and Isidewith
Keywords: Cidadania; Expressão política; Conversação online; Portais web; Citizenship; Political expression; Online conversation; Web portals